Promotion of Weather Resilient Technologies, Practices, and Services: Bajra Crop - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Improved/resilient agricultural practices, services and technologies for Bajra crop cultivation, were promoted in Mathura district of Uttar Pradesh, India